2019
DOI: 10.1021/acs.inorgchem.9b00963
|View full text |Cite
|
Sign up to set email alerts
|

Homochiral BINAPDA-Zr-MOF for Heterogeneous Asymmetric Cyanosilylation of Aldehydes

Abstract: A new homochiral BINAPDA-Zr-MOF was prepared by a new chiral organic linker of (R)-4,4′-(6,6′-dichloro-2,2′-diethoxyl-[1,1′-binaphthalene]-4,4′-diyl)­dibenzoic acid (R -L) and ZrCl4 under solvothermal conditions. Its structure was determined by Pawley refinement on the basis of the measured PXRD pattern determined for BINAPDA-Zr-MOF, and it showed that the obtained chiral MOF crystallized in the F23 space group with the same topological structure as that of UiO-66. The obtained BINAPDA-Zr-MOF can be a very act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 55 publications
0
23
1
Order By: Relevance
“…The ligand H 2 L 2 decorated with crown ether groups was achieved from H 2 L 1 by three steps with 52% overall yield. In addition, H 2 L 3 was synthesized as described in previous literature . Full descriptions of the syntheses and characterizations for H 2 L 1 –H 2 L 3 and intermediates are provided in Supporting Information (Figures S1–S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand H 2 L 2 decorated with crown ether groups was achieved from H 2 L 1 by three steps with 52% overall yield. In addition, H 2 L 3 was synthesized as described in previous literature . Full descriptions of the syntheses and characterizations for H 2 L 1 –H 2 L 3 and intermediates are provided in Supporting Information (Figures S1–S11).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 L 1 by three steps with 52% overall yield. In addition, H 2 L 3 was synthesized as described in previous literature 60. Full descriptions of the syntheses and characterizations for H 2 L 1 − H…”
mentioning
confidence: 99%
“…[ 71–76 ] In other words, this polymer is hydrophilic and dissolves in water when the temperature is below the T c at ≈32 °C, yet it also forms aggregates. [ 77–79 ] Using this unique feature, Karmakar et al ( Figure 5 ) reported that a chromium‐based MOF (MIL‐101) modified by PNIPAM exhibited thermo‐responsive water capture and release behavior. [ 80 ] Forty percent water content could be captured by a MOF at 96% RH and 25 °C.…”
Section: Single Stimulus Mofsmentioning
confidence: 99%
“…This is largely due to their robustness and insoluble nature in most of the common organic solvents. The important organic transformations for which CPs have been developed and employed as heterogeneous catalysts include cyanosilylation of aldehydes or ketones [7], Knoevenagel condensation [8], oxidation of alkanes, alcohols or olefins [9], Henry reaction [10,11], ring-opening of epoxides [12], transesterification [13], cascade [14] reactions, etc.…”
Section: Introductionmentioning
confidence: 99%